Characterization of Biosurfactant Produced during Degradation of Hydrocarbons Using Crude Oil As Sole Source of Carbon - Patowary, Kaustuvmani; Patowary, Rupshikha; Kalita, Mohan C.; Deka, Suresh (Frontiers in Microbiology, 2017)
Production and spillage of petroleum hydrocarbons which is the most versatile energy resource causes disastrous environmental pollution. Elevated oil degrading performance from microorganisms is demanded for successful microbial remediation of those toxic pollutants. The employment of biosurfactant-producing and hydrocarbon-utilizing microbes enhances the effectiveness of bioremediation as biosurfactant plays a key role by making hydrocarbons bio-available for degradation. The present study aimed the isolation of a potent biosurfactant producing indigenous bacteria which can be employed for crude oil remediation, along with the characterization of the biosurfactant produced during crude oil biodegradation. A potent bacterial strain Pseudomonas aeruginosa PG1 (identified by 16s rDNA sequencing) was isolated from hydrocarbon contaminated soil that could efficiently produce biosurfactant by utilizing crude oil components as the carbon source, thereby leading to the enhanced degradation of the petroleum hydrocarbons. Strain PG1 could degrade 81.8% of total petroleum hydrocarbons (TPH) after 5 weeks of culture when grown in mineral salt media (MSM) supplemented with 2% (v/v) crude oil as the sole carbon source. GCMS analysis of the treated crude oil samples revealed that P. aeruginosa PG1 could potentially degrade various hydrocarbon contents including various PAHs present in the crude oil. Biosurfactant produced by strain PG1 in the course of crude oil degradation, promotes the reduction of surface tension (ST) of the culture medium from 51.8 mN m-1 to 29.6 mN m-1, with the critical micelle concentration (CMC) of 56 mg L-1. FTIR, LC-MS and SEM-EDS studies revealed that the biosurfactant is a rhamnolipid comprising of both mono and di rhamnolipid congeners. The biosurfactant did not exhibit any cytotoxic effect to mouse L292 fibroblastic cell line, however, strong antibiotic activity against some pathogenic bacteria and fungus was observed.